2019
DOI: 10.5539/ass.v15n7p49
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of University Dropout: A Case of Thailand

Abstract: Student dropout is a growing concern for educational institutions across the world and extensive research on this issue has been done in past few decades. In this study, we analyzed the determinants of student propensity to dropout at Prince of Songkla University, Pattani campus. The data comprised 10,377 students enrolled between the 2007 and 2011 academic years. Variables included in the analysis were admission year, faculty, gender-religion, first semester GPA and admission type. The overall dropout rate ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…51 The nature of college experiences, which is viewed as an outcome of the interaction among student goals, self-efficacy, sense of belonging and perception towards the curriculum, can either enhance or diminish student motivation. 52 Research attests that universities are trying to support students emotionally by providing them with free counselling services offered by academic advisors and psychologists. It is well documented that the COVID-19 pandemic instilled fear in students and caused them to be stressed, anxious and psychological traumas that affected most students and the general populace's mental health.…”
Section: Mitigation Strategies To Counter Factors Driving University ...mentioning
confidence: 99%
“…51 The nature of college experiences, which is viewed as an outcome of the interaction among student goals, self-efficacy, sense of belonging and perception towards the curriculum, can either enhance or diminish student motivation. 52 Research attests that universities are trying to support students emotionally by providing them with free counselling services offered by academic advisors and psychologists. It is well documented that the COVID-19 pandemic instilled fear in students and caused them to be stressed, anxious and psychological traumas that affected most students and the general populace's mental health.…”
Section: Mitigation Strategies To Counter Factors Driving University ...mentioning
confidence: 99%
“…Before upgrades, the Rajabhat were teacher training institutes, and the Rajamangala were focused technical institutes. However, Tentshol, McNeil and Tongkumchum (2019) showed that 24% of students drop out of university. The changing demographics (fewer young people) and the number of available places mean that universities accept students who may not be suited to their programs.…”
Section: Literaturementioning
confidence: 99%
“…In regards to the academic context another influential factor emerging is the -wrong‖ subject choice. The latest consists of a reason for students' early -departure‖ from their studies, highlighting the variations in the dropout rates per university school (Tentshol et al, 2019). In terms of the university dropout, an additional significant factor of influence is the professor's role; indicatively, according to Hall (1999) it took students more than four years to graduate due to their dissatisfaction with the work of the teaching staff (Hall, 1999;Sneyers & De Witte, 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%